Comparison of Post-Operative Symptom Severity (PoSSe) Scores in patients undergoing Mandibular Third Molar surgery in Ile-Ife, Nigeria - Olufemi Ogundipe; Azuka Njokanma (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: The Post-Operative Symptom Severity (Posse) score is useful in the assessment of patients after third molar surgery. Objective: To evaluate patients' perceptions of quality of life after surgical extraction of an impacted mandibular third molar by comparing their Post-operative Symptom Severity (PoSSe) scores at Post-operative Weeks (POW) 1 and 4. Methods: Seventy patients (age 18 to 35 years) at the Out-Patient Department were enrolled in a prospective study prior to surgical removal of third molars. Each patient was given a PoSSe questionnaire to be completed at POW 1 and POW 4. The scale assessed recovery in seven key domains on patients' subjective feeling about pain, eating, speech, sensation, appearance, sickness and interference with daily activities. Results: All but one patient returned completely filled questionnaires. The mean age of the study population was 25.7 ± 4.5 years. The mean PoSSe score at POW 1 and POW 4 were 35.0 ± 7.2 and 33.2 ± 6.9 respectively with statistically significant difference (p = 0.010). The PoSSe score was higher among males compared to females at POW 1 (37.2 ± 7.6 vs 33.5 ± 6.6) and also higher among males at POW 4 (33.8 ± 9.4 vs 32.7 ± 4.6). Conclusion: The severity of symptoms was perceived to be worse at POW 1 when compared to POW4 but the symptoms were still severe at POW4. There is a need for surgeons need to pay more attention to management of symptoms in the post-operative intermediate period.